Will the Strong Dollar Trigger a Global Recession? - Steven B. Kamin (American Enterprise Institute (AEI), 2022)
In recent months, as inflation has stubbornly refused to back down and the Federal Reserve threatens ever more monetary tightening, a fearful narrative has taken hold: Rising U.S. interest rates are boosting the dollar to record levels, forcing cheaper currencies and higher import costs onto economies already struggling with skyrocketing energy and food prices. In order to keep the lid on soaring inflation, foreign central banks must further tighten their own monetary policies, pushing the world into a global recession. Moreover, higher U.S. interest rates and a stronger dollar are putting special pressure on emerging market economies (EMEs), which must repay their dollar debts with ever-cheaper local currencies. There is more than a grain of truth in these concerns. A rising dollar helps cool the U.S. economy but inevitably involves exporting a certain amount of inflation abroad. And, historically, tighter Fed policies have meant plunging currencies, rising credit spreads, and disruptive capital outflows for EMEs. However, much of the current discussion exaggerates the role of Fed tightening and dollar appreciation in darkening prospects for the world economy. In this note, I set the record straight with the following findings: 1. Contrary to the impression conveyed in the media, the Fed has not been exceptionally aggressive in its response to rising inflation. It started tightening later than many central banks, and the extent of its tightening has been in line with the actions of other central banks. 2. The strong dollar is hurting EMEs by less than is generally believed. The dollar has risen much more against the currencies of the advanced economies than those of EMEs, and average credit spreads across all EMEs have remained contained. 3. The role of the strong dollar in boosting inflation abroad has been exaggerated. Because nearly all currencies have fallen against the dollar, each foreign economy's "multilateral exchange rate" -that is, its average exchange rate against all of its trading partners-has fallen by much less than its "bilateral" rate against the dollar. In consequence, the correlation between falling currencies and rising inflation around the world has been weak.
Keywords: 330